Theoretical and Experimental Research on Switching Optimization of No. 9 Single Turnout with 60-kg/m Rails - Pu Wang (MDPI AG, 2021)
Based on the necessity of optimizing the structure of No. 9 single turnouts of 60-kg/m rails, we addressed the issues associated with existing turnout switching design methods. Based on finite element analysis, we established a refined calculation model for turnout switching. The model can determine the plane alignment of a switch rail separated from the stock rail based on the actual force acting upon the switch rail. The obtained plane alignment is consistent with the actual situation and is thus reliable. Based on the established turnout switching model, the minimum flangeway width and dynamics between the strokes of the first and second traction points under different conditions were analyzed by numerical simulations. Accordingly, we propose an optimized scheme that takes 160 mm and 85 mm as the stroke value for the first and second traction points, respectively. The scheme helps to meet the requirements for minimum flangeway width while making the deformation of the switch rail more even and therefore minimizing the traction power. Based on the proposed design, trial production and laying of the new No. 9 single turnout with a 60-kg/m rail was conducted, and a switching test was performed. The switching forces at the first and second traction points of the new No. 9 turnout were approximately 1200 and 2000 N, respectively, which were higher than those of existing No. 9 turnouts with 60-kg/m steel rails. Besides, the minimum flangeway width satisfies the requirement for safe vehicle passage with a safety margin of 3–5 mm. The test results proved the effectiveness of the proposed turnout switching design method and parameter optimization scheme.